Dampak Implementasi Kurikulum Merdeka Terhadap Pengembangan Potensi Pesera Didik - Ningtyas, Pranistya Dwi Ayu Mutiara; Juliantari, Ni Kadek (Cetta: Jurnal Ilmu Pendidikan, 2022)
The latest effort in education reform in Indonesia of the independent curriculum, which offers schools more freedom in using teaching and evaluation methods to students. The purpose of this studi is to find out how the implementation of students’ potential. In this studi, using a descriptive case studi approach. This approach focuses on the actual problem as the research progresses. The results show that the independent curriculum is an important step towards inclusive, relevant, and sustainable education. Provide students with the opportunity to develop according to their potential. The impact on the development of students’ potential is very significant, covering several important aspects, in creating a more inclusive learning environment and focusing on developing the potential of individual. 1) The independent curriculum provides freedom of learning, 2) Project-based learning approach, and 3) The is strengthening character, literacy and skills as a solid foundation for developing student potential.